Role of Socioeconomic Uncertainty on Foreign Direct Investment (FDI) Inflows and Economic Growth in ASEAN - Marasanti, Andi Tiara Putri; Verico, Kiki (Centre for Business and Diplomatic Studies (CBDS) Bina Nusantara University, 2023)
The interconnectedness begins with active trade and foreign investment flowing to the host country, making the economies in the world integrated into one another. Unfortunately, the rise of interconnectedness has sky-rocketed uncertainty. Economists then build the considered socioeconomic index, namely the World Uncertainty Index (WUI). This research aims to determine whether such an index can affect Foreign Direct Investment (FDI) inwards and economic growth, especially in ASEAN. We use yearly data of FDI inflows, economic growth, and WUI as a proxy for the global level of domestic uncertainty, inflation, and real effective exchange rate from 2015 to 2019 for each ASEAN member state. We estimate a System Generalized Method of Moments (Sys-GMM) to see the dynamic relationship and the short- and long-run effect of the socioeconomic uncertainty proxies with respect to FDI inflows and economic growth. The results show that the uncertainty index with respect to FDI inflows and growth has been negative and significant. Meanwhile, only FDI inflows sensitively respond to socioeconomic uncertainty in the long run, despite the growth for ASEAN member state.